Rape Myth Acceptance Among Prospective Criminal Justice Professionals - Kim, Bitna (Women & criminal justice, 2020)
To examine the Rape Myth Acceptance (RMA) in undergraduate criminology and criminal justice (CCJ) sample, we surveyed 414 CCJ undergraduate students at a large northeastern public university. In this study, CCJ majors, especially those who desire to work in law enforcement, held high levels of patriarchal beliefs and RMA. Although CCJ majors took several classes on sexual assault/rapes and victimology, and they also evaluated the quality of such courses positively, the multivariate analysis found no significant educational effect on RMA while controlling other variables. We then discuss these findings and offer suggestions for CCJ curricula that may assist our prospective CJ professionals in maintaining and upholding a fair and just CJ system.